The red address book [large type] - Lundberg, Sofia, 1974- (Thorndike Press, a part of Gale, a Cengage Company, 2019)
"Written with love, told with joy. Very easy to enjoy."--Fredrik Backman, author of A Man Called Ove The global fiction sensation--publishing in 28 countries around the world--that follows 96-year-old Doris, who writes down the memories of her eventful life as she pages through her decades-old address book. But the most profound moment of her life is still to come... Meet Doris, a 96-year-old woman living alone in her Stockholm apartment. She has few visitors, but her weekly Skype calls with Jenny--her American grandniece, and her only relative--give her great joy and remind her of her own youth. When Doris was a girl, she was given an address book by her father, and ever since she has carefully documented everyone she met and loved throughout the years. Looking through the little book now, Doris sees the many crossed-out names of people long gone and is struck by the urge to put pen to paper. In writing down the stories of her colorful past--working as a maid in Sweden, modeling in Paris during the 30s, fleeing to Manhattan at the dawn of the Second World War--can she help Jenny, haunted by a difficult childhood, unlock the secrets of their family and finally look to the future? And whatever became of Allan, the love of Doris's life? A charming novel that prompts reflection on the stories we all should carry to the next generation, and the surprises in life that can await even the oldest among us, The Red Address Book introduces Sofia Lundberg as a wise--and irresistible--storyteller.